2022
DOI: 10.3390/brainsci12050541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcranial Direct Current Stimulation on Endurance Performance in Elite Female Rowers: A Pilot, Single-Blinded Study

Abstract: Endurance, which is dependent at least partly upon the activation of the brain cortex, is important for performance in rowing. Transcranial direct current stimulation (tDCS) has shown benefits for endurance, but its effects on the endurance performance of elite rowing athletes are unknown, and are examined in this study. Eight elite female rowers completed 5 km of rowing on an ergometer following stimulation of the tDCS and sham over motor cortices. Each session lasted 20 min and the current was set at 2.2 mA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Athletes were experienced in various sports disciplines: cycling [16, 29, 35, 36, 41], swimming [37, 39, 43], triathlon [30], rowing [41, 42], bodybuilding [31], resistance training [38], basketball [40], parkour [3], taekwondo [17, 32] and pistol-shooting [33]. Additionally, some studies reported that athletes competed at the regional [39], national [17, 32, 37, 42, 43] and/or international level [17, 30, 32, 37]. For an overview of investigated sport-specific motor performances in each study, please see Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Athletes were experienced in various sports disciplines: cycling [16, 29, 35, 36, 41], swimming [37, 39, 43], triathlon [30], rowing [41, 42], bodybuilding [31], resistance training [38], basketball [40], parkour [3], taekwondo [17, 32] and pistol-shooting [33]. Additionally, some studies reported that athletes competed at the regional [39], national [17, 32, 37, 42, 43] and/or international level [17, 30, 32, 37]. For an overview of investigated sport-specific motor performances in each study, please see Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…For an overview of investigated sport-specific motor performances in each study, please see Table 1. Sport disciplines were categorized in the following performance domains: endurance (cycling [16, 29, 35, 36, 41], swimming [37, 39, 43], triathlon [30], rowing [41, 42]), strength (bodybuilding [31], resistance training [38]) & visuomotor skill (basketball [40], parkour [3], taekwondo [17, 32], pistol-shooting [33]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations